FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE DI JEJARING SOSIAL FACEBOOK - Pramono Hari Adi (JBIMA (Jurnal Bisnis dan Manajemen), 2014)
This research purposes is to examine the factors influence online purchase decision on Facebook. The data was all primary which collected through personal interview in the form of questionnaire to 100 sample using cluster sampling method. To examine the hypothesis a multiple linear regression, F test & t test is applied. The result of this research shows that trust, easy of use and information quality have positive effect to online purchase, while risk have a negative effect to online purchase.